PERANCANGAN APLIKASI PENJUALAN BERBASIS DESKTOP PADA PT. QUANTUM PROPRINT INDONESIA - Geoffrey Valhart Harioyno; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
PT Quantum Proprint Indonesia is a company that operates in the printing industry. PT Quantum Proprint Indonesia prints products like business cards, brochures and flyers, posters, calendars, etc. As a company that sells printing services, PT Quantum Proprint Indonesia records every sale for bookkeeping purposes. This process generates a work order, receipts, and bills; all of it is done manually by hand. This presents a few problems, such as the durability of the physical records which are prone to water damage or even general wear and tear, to organizing the records themselves. For example: if a customer wants a repeat order, finding the record with the same order is going to be more difficult with a physical format. Therefore a desktop-based application will be made to alleviate this problem. This application is intended to ease the management of records and increase its accuracy. This application will be made using Java as the programming language with Java Swing as the GUI. MySQL will be used as the database.